Initiation of pharmacotherapy for post-traumatic stress disorder among veterans from Iraq and Afghanistan: a dimensional, symptom cluster approach. Issue 5 (September 2016) - Harpaz-Rotem, Ilan; Rosenheck, Robert; Mohamed, Somaia; Pietrzak, Robert; Hoff, Rani
Abstract : Background: The pharmacological treatment of post-traumatic stress disorder (PTSD) is extremely challenging, as no specific agent has been developed exclusively to treat this disorder. Thus, there are growing concerns among the public, providers and consumers associated with its use as the efficacy of some agents is still in question. Aims: We applied a dimensional and symptom cluster-based approach to better understand how the heterogeneous phenotypic presentation of PTSD may relate to the initiation of pharmacotherapy for PTSD initial episode. Method: US veterans who served in the conflicts in Iraq and Afghanistan and received an initial PTSD diagnosis at the US Veterans Health Administration between 2008 and 2011 were included in this study. Veterans were followed for 365 days from initial PTSD diagnosis to identify initiation for antidepressants, anxiolytics/sedatives/hypnotics, antipsychotics and prazosin. Multivariable analyses were used to assess the relationship between the severity of unique PTSD symptom clusters and receiving prescriptions from each medication class, as well as the time from diagnosis to first prescription. Results: Increased severity of emotional numbing symptoms was independently associated with the prescription of antidepressants, and they were prescribed after a substantially shorter period of time than other medications. Anxiolytics/sedatives/hypnotics prescription was associated with heightened re-experiencing symptoms and sleep difficulties. Antipsychotics were associated with elevated re-experiencing and numbing symptoms and prazosin with reported nightmares. Conclusions: Prescribing practices for military-related PTSD appear to follow US VA/DoD clinical guidelines. Results of this study suggest that a novel dimensional and symptom cluster-based approach to classifying the phenotypic presentation of military-related PTSD symptoms may help inform prescribing patterns for PTSD.